If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 4x = x + -6 Reorder the terms: 5 + 4x = -6 + x Solving 5 + 4x = -6 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 5 + 4x + -1x = -6 + x + -1x Combine like terms: 4x + -1x = 3x 5 + 3x = -6 + x + -1x Combine like terms: x + -1x = 0 5 + 3x = -6 + 0 5 + 3x = -6 Add '-5' to each side of the equation. 5 + -5 + 3x = -6 + -5 Combine like terms: 5 + -5 = 0 0 + 3x = -6 + -5 3x = -6 + -5 Combine like terms: -6 + -5 = -11 3x = -11 Divide each side by '3'. x = -3.666666667 Simplifying x = -3.666666667
| 2753-3456+13= | | 2(x-7)=327 | | 2nm+5=3 | | 8(y+5)=y(10) | | 6x^2+9=33 | | 10+q+8q+17=90 | | 3(-4n-9)=21 | | 2(x-7)=327(7-x) | | Ln(x^2-20)=lnX | | 8-(2y+9)=3(4y+-5) | | 4x+2(x+6)=30 | | 5x-25=x | | 3x+8+16+x+17+20=52 | | 3(-4x+5)=12 | | 2+x=x-15-2 | | 8d-.333(6-9d)=42 | | 6x(12)=4(18) | | 12m+150=1138 | | -6b-6=6-b-3b | | 12k-20-5=1k+4 | | x+(-2x)=-4 | | B-24=52 | | 15+5x=90 | | 5y+3=2y+5 | | 2(x+8)=-(x+3) | | 5y-1=49 | | 4A+100C=2 | | 75=-5(-3*4x) | | 6Y-2=5Y-2 | | A+30B=0 | | -X-7=-2X-5 | | t-3=36 |